BACILLUS AMYLOLIQUEFACIENS - A NOVEL PGPR STRAIN ISOLATED FROM JUTE BASED CROPPING SYSTEM - S. K. BHATTACHARYYA,; C. SENGUPTA,; N. K. ADHIKARY,; J. TARAFDAR, (The Bioscan, 2014)
The present investigation was made to assess the antagonism of new potential bacterial isolates, Bacillus amyloliquefaciens of plant growth promoting rhizobacteria to control Macrophomina Phaseolina disease complex of jute. Bacillus spp. are well known rhizosphere residents of many crops and usually show plant growth promoting activities that include bio control capacity against some phytopatogenic fungi. Amongst the isolated microorganisms, three in which one Bacillus and two others were initially selected based on dual culture technique, production of volatile substance (HCN) in NA, indication towards phytohormone viz. indole 3 acetic acid along with siderophore production. Among the isolated strains Bacillus amyloliquefaciens showed the best effect in phosphate solubilisation efficiency (73.33%), seed germination (96.66%) and seedling growth of jute, almost near the highest ability to pathogen inhibition (74.26%), reduction of stem rot disease severity (62.9%) in the green house test. The same strain was unique compared to all parameters and enhanced the activity of defence enzyme peroxidase (PO) even after challenge inoculation. The results of our present finding has the evidence of new and novel isolate of Bacillus amyloliquefaciens which has tremendous potentiality to control notorious pathogen, M. phaseolina, and also plays unique role in plant growth promoting activities in jute.